1987
DOI: 10.1080/09670878709371135
|View full text |Cite
|
Sign up to set email alerts
|

Damage to crops byMicrotermes najdensis (Isoptera, Macrotermitinae)in irrigated semi‐desert areas of the Red Sea coast 1. The Tihama region of the Yemen Arab Republic

Abstract: Microtermes najdensis is widely distributed throughout irrigated cropping areas of the Tihama region in Yemen Arab Republic. It is subterranean and damages young and mature plants by penetrating the root system and ultimately the stem, causing wilting and death. Surveys showed that plant-mortality without termite control ranged from 2-63% (average 20-30%) in cotton and maize. Pepper, okra and tomato were attacked less severely (average mortality of 10-20%). Tobacco, sorghum, millet and most vegetables suffered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…Les résidus de culture restés au sol, source de nourriture, stimulent la recolonisation des champs par les termites champignonnistes (Wood et al, 1980 ;Tondoh, 1992 ;Mora et al, 1996 ;Sileshi et al, 2005). Par ailleurs, Wood et al, (1977Wood et al, ( et 1980 au Nigeria sur le maïs, Kumar & Veeresh (1990) en Inde sur le blé, Wood et al, (1987) au Yémen sur le coton ont montré que les attaques des termites sont peu importantes la première année (1-2%), mais qu'elles évoluent avec le temps sur les parcelles non traitées. Au niveau du maïs, le mode d'attaque des Microtermes, Ancistrotermes, Amitermes, Pseudacanthotermes, Trinervitermes est similaire à ceux observés par Wood et al, (1980), Cowie et Wood (1989) et Cissé (1991).…”
Section: Discussionunclassified
“…Les résidus de culture restés au sol, source de nourriture, stimulent la recolonisation des champs par les termites champignonnistes (Wood et al, 1980 ;Tondoh, 1992 ;Mora et al, 1996 ;Sileshi et al, 2005). Par ailleurs, Wood et al, (1977Wood et al, ( et 1980 au Nigeria sur le maïs, Kumar & Veeresh (1990) en Inde sur le blé, Wood et al, (1987) au Yémen sur le coton ont montré que les attaques des termites sont peu importantes la première année (1-2%), mais qu'elles évoluent avec le temps sur les parcelles non traitées. Au niveau du maïs, le mode d'attaque des Microtermes, Ancistrotermes, Amitermes, Pseudacanthotermes, Trinervitermes est similaire à ceux observés par Wood et al, (1980), Cowie et Wood (1989) et Cissé (1991).…”
Section: Discussionunclassified
“…and Ancistrotermes spp. have diffuse subterranean nests and attack plants from below ground by entering the root system and tunnelling up into the stem, hollowing it out and frequently filling it with soil Sands, 1973aSands, , 1973bWood et al, 1987). These characteristic modes of attack grade into each other and one genus may adopt more than one of them.…”
Section: Termite Diversitymentioning
confidence: 99%
“…The relationship between foraging activity, plant mortality and yield loss varies with the kind of crop (Wood et al, 1987). For groundnuts in Nigeria, Johnson et al, (1981) found a relationship between stand and yield losses, while in cotton there appears to be no clear relationship.…”
Section: Plant Mortality and Yieldmentioning
confidence: 95%
“…Foraging activity in various termite species is influenced by irrigation (Wood et al, 1987), soil water content and rainfall (Ueckert et al, 1976;Johnson er al., 1981), temperature (Badawi ef a/., 1984) and possibly by internal activity rhythms (Bouillon, 1970).…”
Section: Foraging Activitymentioning
confidence: 99%